Avoiding Blindness to Health Status: A New Class of Health Achievement and Inequality Indices - Makdissi, Paul; Yazbeck, Myra (Université d'Ottawa | University of Ottawa, 2012)
This paper argues that health transfers from an individual at a lower rank in the health distribution to a person at a higher rank may decrease the concentration index if the former has a slightly higher income. The concentration index, being mainly focused on the socio-economic dimension of health inequality, can produce such counter-intuitive results that overlook the pure health inequality aversion of the planner. Building on Atkinson (1970), Yitzhaki (1983) and Wagstaff (2002), this paper presents a simple new class of health achievement and health inequality indices that overcomes the above mentioned problem. / Cet article propose argue qu’un transfert de santé d’un individu vers un autre situé à un rang plus élevé de la distribution de santé peut faire diminuer l’indice de concentration si le premier individu a un revenu légèrement supérieur. Cet indice, en se concentrant exclusivement sur la dimension socioéconomique des inégalités de santé peut produire ce genre de résultat contre-intuitif puisqu’il est totalement insensible aux inégalités pures de santé. Cet article construit sur les apports d’Atkinson (1970), Yitzhaki (1983) et Wagstaff (2002) afin de proposer une nouvelle classe d’indices d’accomplissement et d’inégalité de santé qui corrige le problème mentionné.
Keywords: Health Inequality; Health achievement; Inégalité de santé; accomplissement en santé